Grandparent-child cohesion, friendship quality, and left-behind children's positive/negative affect in rural China. (September 2022) - Zhao, Jingxin; Ge, Jing; Li, Qianyu
This study examined the roles of grandparent-child cohesion and friendship quality in left-behind children's positive and negative affect compared with non-left-behind children. Data from 557 participants indicated that grandparent-child cohesion and friendship quality predicted children's emotional adaptation. Friend trust and support and intimate exchange had a stronger predictive effect on positive affect among non-left-behind children. Moreover, the interaction effects between grandparent-child cohesion and friendship quality on children's positive affect supported the reinforcement model, while the interaction effects on negative affect supported the reinforcement model among left-behind children but supported the compensation model among non-left-behind children.